2014
DOI: 10.1002/2014ja019879
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a reconnection layer poleward of the cusp: Extreme density asymmetry and a guide field

Abstract: We present Polar observations of a reconnection layer during an inbound pass at high northern latitudes. The interplanetary field of 20 nT pointed strongly northward continuously for 13 h. Reverse polar cap convection observed repeatedly by the DMSP F13 satellite provided direct evidence of continued reconnection. Polar observed sunward and southward jets. The event was hallmarked by a density asymmetry ≈140 and moderate guide field. Disturbances in fields and plasma were much more intense on the magnetosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 68 publications
5
9
0
Order By: Relevance
“…On the magnetosheath side of this enhancement we see a region with negative E N of 1 to 2 mV/m. The observation of a stronger Hall electric field on the magnetosphere side is consistent with Hall electric fields seen in simulations of asymmetric reconnection [ Mozer et al , ; Pritchett and Mozer , ; Mozer and Pritchett , ; Muzamil et al , ]. In contrast to symmetric reconnection, the Hall electric field in asymmetric does not point toward the X line but rather toward the flow stagnation point, which for asymmetric reconnection is expected to be located on the magnetosphere side of the X line [ Cassak and Shay , ; Birn et al , ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…On the magnetosheath side of this enhancement we see a region with negative E N of 1 to 2 mV/m. The observation of a stronger Hall electric field on the magnetosphere side is consistent with Hall electric fields seen in simulations of asymmetric reconnection [ Mozer et al , ; Pritchett and Mozer , ; Mozer and Pritchett , ; Muzamil et al , ]. In contrast to symmetric reconnection, the Hall electric field in asymmetric does not point toward the X line but rather toward the flow stagnation point, which for asymmetric reconnection is expected to be located on the magnetosphere side of the X line [ Cassak and Shay , ; Birn et al , ].…”
Section: Discussionsupporting
confidence: 68%
“…For symmetric reconnection, the Hall magnetic field consists of a quadrupolar signature in the out‐of‐plane magnetic field [ Nagai et al , ]. Two‐dimensional PIC simulations of asymmetric reconnection have found that the Hall magnetic field tends to be stronger on the magnetosheath side [ Pritchett , ; Pritchett and Mozer , ; Muzamil et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetries introduce various changes in the structure of the IDR prevailing under symmetric conditions. Thus, for example, the quadrupolar Hall magnetic field structure becomes dipolar (see, e.g., Mozer, Pritchett, et al, 2008;Muzamil et al, 2014;Pritchett, 2008). The addition of a guide field, that is, a magnetic field component along the direction of the X line, adds complexities to the structure by, for example, giving rise to differences in the Hall B field in the two outflow regions (e.g., Pritchett & Mozer, 2009; see also review by Eastwood et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown observationally that reconnection slows locally when a plume reaches the dayside reconnection site [ Walsh et al , , ]. Predictions of the substructure of the diffusion region have been observed [ Graham et al , ; Muzamil et al , ]. The Cluster satellites were used to compare the theory with multiple events, showing a correlation between the predictions and the data [ Wang et al , ] (though see the paper for further discussion).…”
Section: Introductionmentioning
confidence: 99%